Extracting the common factor in parentheses

šŸ†Practice common factoring

Common Factor Extraction Method:
Identify the largest free number that we can extract.
Then, let's move on to the variables and ask what is the least number of times the X X appears in any element?
Multiply the free number by the variable the same number of times we have found and we will obtain the greatest common factor.

To verify that you have correctly extracted the common factor, open the parentheses and see if you have returned to the original exercise.

Start practice

Test yourself on common factoring!

einstein

Solve the following problem:

\( x^2-x=0 \)

Practice more now

Factoring out the greatest common factor is the first operation we try to carry out when we want to break down an expression into factors.
We can remove from the parentheses a factor that is common to both elements and leave inside a simple and comfortable expression.
The greatest common factor is the largest factor that is completely common to both elements.


Operation steps for extracting the common factor

Notice which is the largest free number we can extract.
Then, let's move on to the unknowns and ask what is the least number of times that X X appears in any element?
Multiply the free number by the unknown the number of times we have found and we will obtain the greatest common factor. To verify that you have extracted the common factor correctly, open the parentheses and see if you have arrived at the original exercise.

Join Over 30,000 Students Excelling in Math!
Endless Practice, Expert Guidance - Elevate Your Math Skills Today
Test your knowledge

Let's look at an example of factoring out the common factor from the parentheses.

8x2+4x=8x^2+4x=
Let's see what is the greatest common factor we can take out, the answer is 44.
Now let's move on to the variable xx. What is the minimum number of times that xx appears in any term? The answer is 11.
Now let's multiply the common factor obtained by the variable the number of times we have found and it will give us the greatest common factor.
That is: 4Ɨx=4x4\times x=4x
Let's take out 4x4x as the common factor and we will obtain:
4x(2x+1)4x(2x+1)
This is our factorization.
When we want to find the solutions we will compare it with00 and it will give us:
4x(2x+1)=04x(2x+1)=0
X=0X=0
ā€‹ā€‹ā€‹ā€‹ā€‹ā€‹ā€‹2x+1=0ā€‹ā€‹ā€‹ā€‹ā€‹ā€‹ā€‹2x+1=0
2x=āˆ’12x=-1
x=āˆ’1/2x=-1/2
Therefore:
x=0,āˆ’1/2x=0,-1/2

Don't worry, as you practice extracting the common factor you will not need to act according to the operation steps as we taught them, you will do the extraction of the common factor intuitively and quickly.


Examples and exercises with solutions on factoring by taking out the common factor from the parentheses

Exercise #1

Solve the following problem:

x2āˆ’x=0 x^2-x=0

Video Solution

Step-by-Step Solution

Shown below is the given equation:

x2āˆ’x=0 x^2-x=0

First note that on the left side we are able to factor the expression using a common factor. The largest common factor for the numbers and letters in this case is x x and this is due to the fact that the first power is the lowest power in the equation. Therefore it is included both in the term with the second power and in the term with the first power. Any power higher than this is not included in the term with the first power, which is the lowest. Hence this is the term with the highest power that can be factored out as a common factor from all terms in the expression. Continue to factor the expression:

x2āˆ’x=0ā†“x(xāˆ’1)=0 x^2-x=0 \\ \downarrow\\ x(x-1)=0

Proceed to the left side of the equation that we obtained in the last step. There is a multiplication of algebraic expressions and on the right side the number 0. Therefore given that the only way to obtain 0 from a multiplication is to multiply by 0, at least one of the expressions in the multiplication on the left side must equal zero,

Meaning:

x=0 \boxed{x=0}

or:

xāˆ’1=0ā†“x=1 x-1=0\\ \downarrow\\ \boxed{x=1}

Let's summarize then the solution to the equation:

x2āˆ’x=0ā†“x(xāˆ’1)=0ā†“x=0ā†’x=0xāˆ’1=0ā†’x=1ā†“x=0,1 x^2-x=0 \\ \downarrow\\ x(x-1)=0 \\ \downarrow\\ x=0 \rightarrow\boxed{ x=0}\\ x-1=0 \rightarrow \boxed{x=1}\\ \downarrow\\ \boxed{x=0,1}

Therefore the correct answer is answer B.

Answer

x=0,1 x=0,1

Exercise #2

x4+2x2=0 x^4+2x^2=0

Video Solution

Step-by-Step Solution

To solve the equation x4+2x2=0x^4 + 2x^2 = 0, we will use the technique of factoring. Let's proceed step-by-step:

First, notice that both terms x4x^4 and 2x22x^2 have a common factor of x2x^2. We can factor x2x^2 out from the equation:

x2(x2+2)=0x^2(x^2 + 2) = 0

Now, to solve for xx, we apply the Zero Product Property, which gives us that at least one of the factors must be zero:

  • x2=0x^2 = 0 or
  • x2+2=0x^2 + 2 = 0

Solving the first case, x2=0x^2 = 0:

x=0x = 0

For the second case, x2+2=0x^2 + 2 = 0, we reach:

x2=āˆ’2x^2 = -2

Since x2=āˆ’2x^2 = -2 has no real solutions (squares of real numbers are non-negative), we can conclude that this equation doesn't provide additional real solutions.

Therefore, the only real solution to the given equation is x=0x = 0.

The correct choice from the provided options is:

x=0 x=0

Answer

x=0 x=0

Exercise #3

Solve the following problem:

x7āˆ’x6=0 x^7-x^6=0

Video Solution

Step-by-Step Solution

Shown below is the given problem:

x7āˆ’x6=0 x^7-x^6=0

First, note that on the left side we are able factor the expression by using a common factor.

The largest common factor for the numbers and letters in this case is x6 x^6 due to the fact that the sixth power is the lowest power in the equation . Therefore it is included both in the term with the seventh power and in the term with the sixth power. Any power higher than this is not included in the term with the sixth power, which is the lowest. Hence this is the term with the highest power that can be factored out as a common factor from all terms in the expression. Continue to factor the expression.

x7āˆ’x6=0ā†“x6(xāˆ’1)=0 x^7-x^6=0 \\ \downarrow\\ x^6(x-1)=0

Proceed to the left side of the equation that we obtained from the last step. There is a multiplication of algebraic expressions and on the right side the number 0. Therefore due to the fact that the only way to obtain 0 from multiplication is to multiply by 0, at least one of the expressions in the multiplication on the left side must equal zero,

Meaning:

x6=0/6x=Ā±0x=0 x^6=0 \hspace{8pt}\text{/}\sqrt[6]{\hspace{6pt}}\\ x=\pm0\\ \boxed{x=0}

(in this case taking the even root of the right side of the equation will yield two possibilities - positive and negative however given that we're dealing with zero, we only obtain one answer)

or:

xāˆ’1=0ā†“x=1 x-1=0\\ \downarrow\\ \boxed{x=1}

Let's summarize the solution of the equation:

x7āˆ’x6=0ā†“x6(xāˆ’1)=0ā†“x6=0ā†’x=0xāˆ’1=0ā†’x=1ā†“x=0,1 x^7-x^6=0 \\ \downarrow\\ x^6(x-1)=0 \\ \downarrow\\ x^6=0 \rightarrow\boxed{ x=0}\\ x-1=0 \rightarrow \boxed{x=1}\\ \downarrow\\ \boxed{x=0,1}

Therefore the correct answer is answer C.

Answer

x=0,1 x=0,1

Exercise #4

4x4āˆ’12x3=0 4x^4-12x^3=0

Solve the equation above for x.

Video Solution

Step-by-Step Solution

Shown below is the given problem:

4x4āˆ’12x3=0 4x^4-12x^3=0

First, note that on the left side we are able factor the expression by using a common factor. The largest common factor for the numbers and variables in this case is 4x3 4x^3 due to the fact that the third power is the lowest power in the equation. Therefore it is included in both the term with the fourth power and the term with the third power. Any power higher than this is not included in the term with the third power, which is the lowest. Hence this is the term with the highest power that can be factored out as a common factor for the variables,

For the numbers, note that 12 is a multiple of 4, therefore 4 is the largest common factor for the numbers in both terms of the expression,

Let's continue to factor the expression:

4x4āˆ’12x3=0ā†“4x3(xāˆ’3)=0 4x^4-12x^3=0 \\ \downarrow\\ 4x^3(x-3)=0

Proceed to the left side of the equation that we obtained in the last step. There is a multiplication of algebraic expressions and on the right side the number 0. Therefore given that the only way to obtain 0 from a multiplication is to multiply by 0, at least one of the expressions in the multiplication on the left side must equal zero,

Meaning:

4x3=0/:4x3=0/3x=0 4x^3=0 \hspace{8pt}\text{/}:4\\ x^3=0 \hspace{8pt}\text{/}\sqrt[3]{\hspace{6pt}}\\ \boxed{x=0}

In solving the equation above, we first divided both sides of the equation by the term with the unknown and then extracted a cube root for both sides of the equation.

(In this case, extracting an odd root for the right side of the equation yielded one possibility)

Or:

xāˆ’3=0x=3 x-3=0\\ \boxed{x=3}

Let's summarize the solution of the equation:

4x4āˆ’12x3=0ā†“4x3(xāˆ’3)=0ā†“4x3=0ā†’x=0xāˆ’3=0ā†’x=3ā†“x=0,3 4x^4-12x^3=0 \\ \downarrow\\ 4x^3(x-3)=0 \\ \downarrow\\ 4x^3=0 \rightarrow\boxed{ x=0}\\ x-3=0\rightarrow \boxed{x=3}\\ \downarrow\\ \boxed{x=0,3}

Therefore the correct answer is answer A.

Answer

x=0,3 x=0,3

Exercise #5

Solve the following problem:

3x2+9x=0 3x^2+9x=0

Video Solution

Step-by-Step Solution

Shown below is the given problem:

3x2+9x=0 3x^2+9x=0

First, note that in the left side we are able to factor the expression by using a common factor. The largest common factor for the numbers and letters in this case is 3x 3x due to the fact that the first power is the lowest power in the equation and therefore is included both in the term with the second power and in the term with the first power. Any power higher than this is not included in the term with the first power, which is the lowest. Therefore this is the term with the highest power that can be factored out as a common factor from all terms for the letters,

For the numbers, note that 9 is a multiple of 3, therefore it is the largest common factor for the numbers in both terms of the expression,

Let's continue to factor the expression:

3x2+9x=0ā†“3x(x+3)=0 3x^2+9x=0 \\ \downarrow\\ 3x(x+3)=0

Proceed to the left side of the equation that we obtained in the last step. There is a multiplication of algebraic expressions and on the right side the number 0. Therefore, given that the only way to obtain 0 from a multiplication is to multiply by 0, at least one of the expressions in the multiplication on the left side must equal zero,

Meaning:

3x=0/:3x=0 3x=0 \hspace{8pt}\text{/}:3\\ \boxed{x=0}

In solving the above equation, we divided both sides of the equation by the term with the variable,

Or:

x+3=0x=āˆ’3 x+3=0 \\ \boxed{x=-3}

Let's summarize the solution of the equation:

3x2+9x=0ā†“3x(x+3)=0ā†“3x=0ā†’x=0x+3=0ā†’x=āˆ’3ā†“x=0,āˆ’3 3x^2+9x=0 \\ \downarrow\\ 3x(x+3)=0 \\ \downarrow\\ 3x=0 \rightarrow\boxed{ x=0}\\ x+3=0\rightarrow \boxed{x=-3}\\ \downarrow\\ \boxed{x=0,-3}

Therefore the correct answer is answer C.

Answer

x=0,x=āˆ’3 x=0,x=-3

Do you know what the answer is?
Start practice